Mircea Eliade: elementos sensoriales en La noche de San Juan : Mircea Eliade: Sensory elements on The Forbidden Forest - Carvajal Arguelles, Ines (Swedish Journal of Romanian Studies, 2026)
The senses are an essential instrument in our perception of the world, as well as in the creation of literary universes. Our paper will analyse how Mircea Eliade reads Bucharest through the senses in his novel The Forbidden Forest. From the nostalgia of exile, Eliade reconstructs his hometown through a mixture of sensory impressions. First among them goes sight, closely linked to time. Time –a most important concept in his work, both academic and literary– is also linked to memory; and memory is also connected to smell. Both approaches –sight and smell– explain the relevance of senses in Eliade’s work.